2018
DOI: 10.18203/2349-2902.isj20180020
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the outcome of perforation peritonitis by using apache II scoring system

Abstract: Background:Peritonitis is inflammation of peritoneum and peritoneal cavity. This study was aimed at predicting morbidity and mortality in patients with peritonitis due to hollow viscous perforation by using APACHE II Scoring system.Methods: This study was conducted in patients admitted as a case of perforation peritonitis in Tertiary centre Dehradun, over the period of 18 months. APACHE II score was calculated and correlated with their symptoms and clinical outcomes regarding morbidity and mortality.Results:In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Our present study is in accordance with the study done by Gupta et al in which most common site of perforation was first part of duodenum, which was similar to the study done by Jhobta et al 9,10 Second most common site according to Gupta et al was ileal (20%) which was again similar to the study done by Jhobta et al in which the incidence of ileal perforation was 22%. 9,10 According to Kumar et al, most common cause of perforation peritonitis was peptic ulcer perforation (36%) followed by typhoid ileal perforation (20%) followed by appendicular perforation (16%). 8 In present study highest incidence of SSI was seen in gastro duodenal perforations, 37.1% in control group and 20% in case group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our present study is in accordance with the study done by Gupta et al in which most common site of perforation was first part of duodenum, which was similar to the study done by Jhobta et al 9,10 Second most common site according to Gupta et al was ileal (20%) which was again similar to the study done by Jhobta et al in which the incidence of ileal perforation was 22%. 9,10 According to Kumar et al, most common cause of perforation peritonitis was peptic ulcer perforation (36%) followed by typhoid ileal perforation (20%) followed by appendicular perforation (16%). 8 In present study highest incidence of SSI was seen in gastro duodenal perforations, 37.1% in control group and 20% in case group.…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with the study done by Gupta et al which shows the peak incidence of 29% of SSI in age group of 17-30 years. 10 This is also in accordance with the study done by LekshmiPriya et al which shows the highest incidence of SSI (24.5%) in age group of 51-60 years. 1 Study done by Basith et al also supports our study and shows that age has a detrimental effect on the outcome of surgery with respect to SSI.…”
Section: Discussionsupporting
confidence: 92%
“…Gupta at el, in their study on 100 patients of perforation peritonitis concluded that for the prediction of death and complications in peritonitis, the physiological reserves of the patient is of great importance. 8 In their study they reported more than 65% mortality in patient with Apache II score of more than 20 and 100% mortality rate in score more than 34. They also observed that more the Apache II scoreless is the Hospital Stay as observed with our results.…”
Section: Discussionmentioning
confidence: 92%
“…6 The risk assessment by important clinical parameter has been extremely useful in evaluating new therapies, in monitoring resources utilization and improving the quality of care. 7,8 Many scoring systems have been found useful in predicting the outcome in critically ill patients, thus allowing application of resources for effective use. 9 Amongst them acute physiology and chronic health evaluation score (APACHE II), simplified acute physiology score (SAPS), sepsis severity score is mostly used and other scores specifically for peritonitis like the Mannheim peritonitis index and the peritonitis index altona II.…”
Section: Introductionmentioning
confidence: 99%
“…8 The study by Agrawal et al of 260 cases reported overall mortality of 10%. 11 Ramachandra et al had a mortality rate of 14%. 10 In our study 6 cases (12%) developed wound infections and 2 (4%) patients developed respiratory complications as postoperative complication.…”
Section: Complicationmentioning
confidence: 99%